Time Dependent Performance of ITER90H-P Fusion Reactor with Considering D-T and D-3He Fuel - S. N. HOSSEİNİMOTLAGH; S. KİANAFRAZ; Sakineh GHADERİ (International Journal of Applied Methods in Electronics and Computers, 2015)
In  thermonuclear  fusion  research  using  magnetic  confinement,  the  tokamak  is  the  leading candidate for achieving conditions required for a reactor. An international experiment, ITER is proposed as the next essential and critical step on the path to demonstrating the scientific and technological feasibility of fusion energy.  ITER is to produce and study plasmas dominated by self-heating.  This  would  give  unique  opportunities  to  explore,  in  reactor relevant  conditions,  the  physics  of  α-particle  heating,  plasma  turbulence  and  turbulent transport, stability limits to the plasma pressure and exhaust of power and particles. Our studies show that in the dynamical state physical quantities are dependent on temperature and time .Each has its own specific variations and also  at the  temperature 70 (Kev) these quantities produce the maximum  fusion gain for  both of fuels D – T and,D- 3 He such that their values are equal to 81.311   for D - T fuel-and the 0.0429 for D- 3 He at one second after occurring fusion t=1s ,respectively.